Bullying in the workplace and its impact on enhancing employee burnout: An exploratory study of the opinions of a sample of employees at the University of Zakho - Dawood, Dalia; Kochar, Jotiar (Humanities Journal of University of Zakho, 2021)
This research seeks to determine the role of the dimensions of bullying in the workplace in promoting job burnout among employees. The University of Zakho was chosen as a field for implementing the practical side. The research was based on a set of main and sub-hypotheses, which were field-tested on (72) of the researched employees. The data was collected through a questionnaire form prepared for this purpose, depending on the analytical and statistical methods available in the (SPSS V.24) program to analyze the correlation and influence between the research variables. The research outcome was to reach to several conclusions, the most important of which was the existence of a positive moral correlation for the independent variable represented by bullying in the workplace and the dependent variable represented by job burnout, as well as the presence of a significant effect of the independent variable on the dependent variable. In light of the conclusions reached, the two researchers presented a set of suggestions, the most important of which is the necessity of ensuring the provision of a supportive and positive organizational climate at work by providing supportive and effective leadership that places employees among its most important priorities.